2020
DOI: 10.1111/ijfs.14451
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive determination of salmon fillet freshness during storage at different temperatures by electronic nose system combined with radial basis function neural networks

Abstract: This study develops a predictive model for determining freshness of salmon fillets during cold storage at different temperatures using electronic nose combined with principal component analysis (PCA) and radial basis function neural networks (RBFNNs). The electronic nose sensed ammonia/amines, hydrocarbons, solvents and aromatics that increased during storage. The concentrations of the volatiles were compared with the increased thiobarbituric acid (TBA), total volatile basic nitrogen (TVB-N), total aerobic bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 24 publications
6
9
0
Order By: Relevance
“…These contributions significantly change up to 60 d, and barely change for 90 and 120 d. The main difference between the 90 and 120 d samples arises from the fuel sample distribution points. These results are similar to those obtained by Jia ( Jia et al, 2020 ). It has also been reported that volatiles are produced in oil, especially esters and alcohols ( Mi et al, 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…These contributions significantly change up to 60 d, and barely change for 90 and 120 d. The main difference between the 90 and 120 d samples arises from the fuel sample distribution points. These results are similar to those obtained by Jia ( Jia et al, 2020 ). It has also been reported that volatiles are produced in oil, especially esters and alcohols ( Mi et al, 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…As shown in the PCA plot of the volatiles identified by GC-MS (Figure 7), PC-1 had a remarkable influence on the large yellow croaker meat samples over the various storage periods, and the day 0 samples differed significantly from those at 60 d (p < 0.05). Indeed, this difference increased further when the storage period was prolonged to 90 and 120 d. This gradual change in the flavor components during storage is similar to previously reported findings for salmon fillets [52]. Overall, our results indicate that the flavor characteristics of large yellow croaker meat were successfully established using GC-IMS for the various storage periods.…”
Section: Pca Of the Characteristic Flavor Compounds Present In Large Yellow Croakersupporting
confidence: 90%
“…Nonanal is the main product of oleic acid oxidation, and the initial sensory threshold value of 4.13 ± 0.02 mg g −1 gradually increased to 5.32 ± 0.02 mg g −1 . More importantly, nonanal greatly contributes to the overall flavour of large yellow croaker oil and imparts the fish oil a waxy, fatty, and floral aroma among other sensory profiles the content of hexanal also changed with the extension of storage time, largely due to linoleic acid oxidation (Jia et al ., 2020). According to a previous study, linoleic acid peroxidation may inhibit free radical activity and reduce the content of volatile components (Song et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%